Digital media preferences in late adolescence: challenges of online engagement and the importance of social support - Kornienko, D.S.; Rudnova, N.A.; Smirnova, Y.K.; Kalimullin, A.M.; Semenov, Y.I. (Socialʹnaâ Psihologiâ i Obŝestvo, 2025)
Context and relevance. The digital socialization of contemporary adolescents is a subject of considerable study interest owing to the profound integration of Internet technology into daily life. The relevance is due to the insufficient study of the links between preferred content, problems arising from the active use of the Internet and social networks, and the role of social support. Objective. To determine the links between digital content and emerging problems in adolescents, as well as to identify the contribution of social support to reducing problems arising from online activity. Methods and materials. The research involved a sample of 1239 Russian adolescents (42,7% male) aged 15-17 years from various areas of the Russian Federation. Questionnaires on digital parental mediation, peer perception, and social media usage were employed to evaluate favored themes in Internet and social network usage, as well as the severity of issues related to digital activity. Correlation, regression, and comparative analysis were employed. Results. A hierarchy of content choices among teenagers was identified: entertainment content (humor, trends) is predominant, succeeded by instructional resources and sports. Girls show greater interest in educational and infotainment content but report greater severity of problems arising from digital activity. Parental and peer support mitigates the adverse consequences of online engagement, whereas parental control exacerbates issues. Conclusions. The prevalence of entertainment material correlates with the severity of issues. The quality of peer interactions is more significant than parental mediation in mitigating the adverse impacts of internet use. Peer assistance mitigates compensating Internet usage. Parental assistance is more efficacious than control in mitigating issues. Контекст и актуальность. Цифровая социализация современных подростков представляет значительный исследовательский интерес в связи с глубокой интеграцией интернет-технологий в повседневную жизнь. Актуальность обусловлена недостаточным изучением связей между предпочитаемым контентом, проблемами, возникающими в результате активного использования интернета и социальных сетей, и ролью социальной поддержки. Цель. Определить связи между цифровым контентом и возникающими проблемами у подростков, а также выявить вклад социальной поддержки в снижение проблем, возникающих в результате онлайн-активности. Методы и материалы. Исследование проводилось на выборке 1239 российских подростков (42,7% юношей) в возрасте 15-17 лет из разных регионов Российской Федерации. Использовались опросники цифровой родительской медиации, восприятия сверстников и использования социальных медиа (для оценки предпочитаемых тем при использовании интернета и социальных сетей и выраженности проблем, связанных с цифровой активностью). Применялись корреляционный, регрессионный и сравнительный анализы. Результаты. Выявлена иерархия предпочитаемого подростками контента: лидирует развлекательный контент (юмор, тренды), затем следуют образовательные материалы и спорт. Девушки проявляют больший интерес к образовательному и информационно-развлекательному контенту, но сообщают о большей выраженности проблем, возникающих в результате цифровой активности. Социальная поддержка родителей и сверстников снижает негативные эффекты онлайн-активности, тогда как родительский контроль усиливает проблемы. Выводы. Доминирование развлекательного контента сочетается с большей выраженностью проблем. Качество связей со сверстниками важнее родительской медиации для снижения негативных эффектов онлайн-активности. Поддержка ровесников предотвращает компенсаторное использование интернета. Родительская поддержка эффективнее контроля в профилактике проблем.